ORAL MUCOSAL CHANGES IN COELIAC DISEASE, DIABETES MELLITUS, AND INFLAMMATORY BOWEL DISEASES – A SYSTEMATIC REVIEW - Ryszard Feret,; Natalia Dymel,; Krzysztof Feret,; Michalina Chodór,; Maciej Kokoszka,; Aleksandra Tomaszewska,; Kinga Karczewska,; Sonia Mojzyk,; Aleksandra Mierniczek,; Aleksandra Ćwirko-Godycka,; Nikola Murawska, (International Journal of Innovative Technologies in Social Science, 2026)
Background: The oral cavity is sometimes referred to as a “diagnostic window” of systemic health, as even subtle systemic disturbances can manifest as changes in the oral mucosa. Coeliac disease, diabetes mellitus, and inflammatory bowel diseases (IBD) are chronic conditions that frequently present with oral mucosal lesions, which may precede or accompany the classical symptoms of these diseases.Aim: To systematically review and compare the oral mucosal changes reported in coeliac disease, diabetes mellitus, and IBD. The most common clinical manifestations are characterized, potential pathophysiological mechanisms are discussed, and the relevance of oral findings for early recognition and monitoring of these systemic diseases is evaluated.Materials and Methods: A systematic literature search was conducted in PubMed and Google Scholar using combinations of English keywords (including “oral mucosa,” “oral manifestations,” “coeliac disease,” “diabetes mellitus,” “inflammatory bowel disease,” “Crohn’s disease,” “ulcerative colitis,” “aphthous ulcers,” “xerostomia,” “oral microbiome,” and “oral–gut axis”). A total of 37 relevant peer-reviewed articles (clinical studies and reviews) were identified and analyzed.Results: The most frequently described oral manifestations in these conditions include recurrent aphthous stomatitis, inflammatory and atrophic changes of the tongue (such as geographic tongue and atrophic glossitis), angular cheilitis, xerostomia, and recurrent opportunistic infections (especially oral candidosis). In coeliac disease, oral lesions (aphthae, glossitis, cheilitis) and dental enamel defects often occur, sometimes even years before diagnosis, and tend to improve after the introduction of a strict gluten-free diet. Diabetes is associated with salivary gland dysfunction leading to dry mouth, elevated salivary glucose, and immune dysfunction – factors that contribute to candidosis, poor wound healing, burning mouth sensations, and an increased incidence of oral ulcers. IBD (Crohn’s disease and ulcerative colitis) can produce a broad spectrum of oral changes: Crohn’s disease in particular is characterized by specific granulomatous lesions (such as persistent lip swelling, mucosal “cobblestoning,” and deep linear ulcers) as well as nonspecific lesions (recurrent aphthae, pyostomatitis vegetans, glossitis, cheilitis). Oral manifestations of IBD are more common in Crohn’s disease and in pediatric patients and can precede intestinal symptoms or correlate with intestinal disease activity.Conclusions: Oral mucosal changes represent an important extraintestinal component of coeliac disease, diabetes, and IBD. They can serve as early warning signs of these disorders or indicators of disease activity and control. Recognition of characteristic oral lesions by dentists and physicians is crucial, as it can expedite diagnosis and prompt timely management (e.g. initiation of a gluten-free diet in coeliac disease or improved glycemic control in diabetes). Regular oral examinations should be an integral part of the care of patients with these conditions. Interdisciplinary collaboration – especially between dentists, gastroenterologists, and diabetologists – is essential for early detection, comprehensive monitoring, and improved patient outcomes.